Pemberdayaan Kader Posyandu dalam Penggunaan Media Edukasi Gizi Bayi/Balita dan Keterampilan Komunikasi di Posyandu Sanggar Waringin, Kelurahan Lok Bahu - Revina Nur Wahidah; Aprilianus Reynaldy Nurak; Abel Jenissa; Kharisya Nur Ainun Nabilah; Maspah; Maura Arielia Nurhaliza; Nur Asma; Sri Dwijayanti Mutiara Sujaya; Zaky Rahmanul Atif; Nur Rohmah; Annisa Nurrachmawati; Lies Permana; Rina Tri Agustini (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Community empowerment is a strategic step to improve the quality of life through increasing the capacity of individuals and communities, especially in the health sector. Posyandu Sanggar Waringin, Lok Bahu Village, faces challenges such as low immunization coverage, lack of community knowledge about nutrition, and high prevalence of preventable diseases. This activity aims to improve the skills of Posyandu cadres in the use of infant and toddler nutrition education media and communication with the community through the Lentera program (Latihan Edukasi dan Komunikasi Kader Mandiri). The research method used a participatory approach with activities including interviews, observations, social mapping, and focus group discussions involving 6 Posyandu cadres. Interventions were conducted through training using educational media and practice of searching for health information from the Ministry of Health website. Evaluation was conducted using pre-test and post-test analyzed by Wilcoxon test. Results showed a significant increase in cadres' knowledge and skills, with a pre-test mean score of 65 increasing to 87.5 in the post-test (p = 0.024). In addition, the training also increased cadres' confidence in presenting nutrition information. This activity succeeded in strengthening the cadres' capacity as community health agents, potentially improving the community's understanding of nutrition and supporting stunting prevention efforts. In conclusion, empowerment through the Lentera program is effective in improving the quality of services at Posyandu Sanggar Waringin, with a focus on nutrition education and communication. The program is expected to create a sustainable positive impact on public health.